THE IMPACT OF ARTIFICIAL INTELLIGENCE ON PERSONALIZED EDUCATION - Jasur Ziyautdinov (Лучшие интеллектуальные исследования, 2024)
Abstract.The integration of Artificial Intelligence (AI) in education has transformed traditional learning paradigms, offering unprecedented opportunities for personalized learning experiences. This paper examines the current state of AI in education, its benefits, challenges, and potential future developments. By analyzing various AI-driven educational tools and their impacts, this research provides insights into how AI can enhance personalized learning, improve student engagement, and foster better educational outcomes. The findings suggest that while AI offers significant advantages, there are also notable challenges that must be addressed to maximize its potential in educational settings. Furthermore, this paper discusses policy implications and offers recommendations for educators and policymakers to effectively integrate AI technologies in educational systems..